Ultra-Processed Food Consumption and its Association with Nutritional Status and Diet-Related Non-Communicable Diseases among School-Aged Children in Lilongwe City, Malawi - Kamanga, Patricia; Zhang, Bo; Kaphera, Samson (International Journal of Child Health and Nutrition, 2022)
In underdeveloped nations like Malawi, Non-Communicable Diseases (NCDs) have received less attention despite increasing NCDs morbidity and incidence rates. NCDs are responsible for 68% of all deaths worldwide each year. Dietary problems are the most common causes of these deaths. In underdeveloped countries, NCDs are responsible for two-thirds of all fatalities. In addition, developing countries account for two out of every three overweight and obese individuals worldwide. Lifestyle factors such as Ultra-Processed Foods (UPFs) consumption is among the causes. Purpose of the Study: To investigate ultra-processed food consumption and its association with nutritional status and diet-related NCDs among school-aged children. Methods: The research was conducted from March-April, 2021, using cross-sectional quantitative methods. A systematic random sample of 382 school-aged children was drawn to collect data. Data were analyzed using the R software package by frequency tables, means, and Chi-Square. Study Findings: Findings suggest high consumption (95.6%) of UPFs, which included flitters, carbonated drinks, processed juice, French fries, and sweets. The study further attributed the high consumption of UPFs to age, residence, price, and availability. In addition, in children who consume high amounts of UPFs, dental problems and high mid-upper arm circumference were common. Conclusion: Prevalence of UPFs is high among school-aged children in Lilongwe city. Although there are reported differences between these two locations, the locations are generally similar. However, age, residence, price, and availability seem to influence UPFs consumption behaviors. In later years, this may predispose children to be cardiovascular and metabolic conditions.